ANALISA POLA DATA HASIL PEMBANGUNAN KABUPATEN MALANG MENGGUNAKAN METODE ASSOCIATION RULE - Sibagariang, Dewi; Auliasari, Karina (MATICS, 2013)
Data of development results in an area divided into several sectors. Each sector has a commodity, government use this data to determine potential comodity in ​​small coverage area. This paper was based on our  research use association rule method,  as we know  this method commonly used in data mining to discover pattern from huge data. Apriori is an algorithm that is implemented on application in this research, this algorithm is used  to  generate strong association information (strong linkage) between commodities in each sector. Support, confidence values and relationship between each commodities in 33 districts Kabupaten Malang displayed by application. From test result showed that more higher  value of confidence and support make the strong relationships between commodity value. Minimum limit value can not support more than 33, because most transaction data which is calculated from the total number of 33 districts in Malang.